Quantification of Aesthetic Composition on Architecture - Paryoko, Vijar Galax Putra Jagat; Widyanti, Nadhila (Sinektika: Jurnal Arsitektur, 2026)
Subjectivity in assessing the aesthetics of a composition in architecture and interior design industry and even education is commonplace today. A less objective assessment can blurry a person's ability of designing building’s aesthetic. In fact, there were quantitative rules for judging the beauty of building appearance in Classical Architecture era. Therefore, the aim of this study is getting quantitative measurement for composition’s aesthetics of building. To achieve that, qualitative research method is used with grounded theory approach. The result shows that aesthetic value can be calculated using a quantitative formula. Despite the formula founded by this study has several weaknesses, this formula was generated from and modestly tested using the questionnaires distributed to various categories of respondents, from public to those who involved in architecture and design education and industry, showing quite high suitability and reliability.